STRATEGI PELATIHAN PADA PEMENTASAN PADUAN SUARA VIRTUAL - Permatasari, Dahlia (Program Studi Pendidikan Musik, 2022)
Dahlia Permatasari, 2023. Strategy for Virtual Choir Training. Essay. Jakarta: Music Education Study Program, Faculty of Languages and Arts, Jakarta State University. The purpose of this research is to find out how the training strategy is staging the Virtual Choir. The training strategy is the success of an organization with systematic and organized procedures in carrying out activities in virtual choral performances. The method used in this research is literature review with a systematic analysis technique of narrative. Data comes from existing research results through Google searches, E-books, Acasemia edu, Semantic Scholar, Oxford Journal, E-JournalUPI, and Youtube sources. The research was conducted in North Bekasi, from September 2021 to December 2022. Total 15 articles were analyzed by making notes in the margins and categorizing tables and summarizing the results of existing research to be combined and then presented with comprehensive facts so that conclusions could be drawn. (Miles and Huberman Prof. Dr. Sugiyono, 2017). The results of this research is indicate that choir training for virtual performances using Zoom Meeting, Google Meet, Cubase, Adobe Premiere, Whatsapp media will be influenced by blended learning methods, demonstration methods, imitation methods, vocal technique materials such as vocalizing, breathing, posture, articulation, and reading songs and choreography. Keywords: Training, Choir, Performance, Virtual